Initial Emergency Management of Trauma: A Literature Review - St. Lutfiah Ahmad; Tirta Swarga; Ade Irna (Newinera Publisher, 2025)
Trauma continues to be one of the leading causes of mortality and disability worldwide, including in Indonesia, with the most critical period occurring within the golden hour. Elevated mortality rates are often linked to delayed medical response, the absence of standardized treatment protocols, and limited healthcare resources. Objective: This review aims to assess the effectiveness of internationally recognized, protocol-driven interventions that have been adapted to the Indonesian context in enhancing trauma care outcomes. A systematic-narrative literature review was conducted in accordance with the PRISMA 2020 guidelines. Sources included SINTA, Scopus, ClinicalKey, as well as conference proceedings and dissertations published between 2023 and 2024. Each study was evaluated for methodological rigor, strength of evidence, and applicability to emergency care settings in Indonesia. Thematic analysis was applied to synthesize the findings. Adaptations of ATLS protocols, interdisciplinary simulation-based training, and the implementation of digital technologies for triage and prehospital communication demonstrated the potential to reduce trauma-related mortality by up to 30%. Furthermore, the early administration of tranexamic acid (TXA), application of tourniquets, and whole blood transfusion proved highly effective in managing severe trauma cases. The integration of international trauma care protocols with locally contextualized innovations and digital health technologies holds significant promise for improving the quality and effectiveness of trauma management in Indonesia.